2016
DOI: 10.1016/j.celrep.2016.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus X Protein Promotes Degradation of SMC5/6 to Enhance HBV Replication

Abstract: SUMMARY The Hepatitis B Virus (HBV) regulatory protein X (HBx) activates gene expression from the HBV covalently closed circular (cccDNA) genome. Interaction of HBx with the DDB1-CUL4-ROC1 (CRL4) E3 ligase is critical for this function. Using substrate-trapping proteomics, we identified the structural maintenance of chromosomes (SMC) complex proteins SMC5/6 as CRL4HBx substrates. HBx expression and HBV infection degraded the SMC5/6 complex in human hepatocytes in vitro and in humanized mice in vivo. HBx target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
267
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(288 citation statements)
references
References 38 publications
15
267
1
5
Order By: Relevance
“…While the hepatocyte innate immune response to HBV is poorly understood [34], it was recently demonstrated that HBV cccDNA is transcriptionally silenced by the Smc5/6 complex when HBx is not present [13,35]. However, it is not known how Smc5/6 suppresses viral gene expression or whether depletion of this complex plays a role in evasion of innate immunity or HBV pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…While the hepatocyte innate immune response to HBV is poorly understood [34], it was recently demonstrated that HBV cccDNA is transcriptionally silenced by the Smc5/6 complex when HBx is not present [13,35]. However, it is not known how Smc5/6 suppresses viral gene expression or whether depletion of this complex plays a role in evasion of innate immunity or HBV pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that HBx hijacks Cul4–DDB1 to promote the proteasomal degradation of Smc5/6 was subsequently confirmed by Murphy et al [21] using a different method from Decorsière et al [20]. Briefly, they expressed tagged HBx in HepG2 cells and treated with MLN4924 to inactivate E3-ubiquitin ligase activity.…”
Section: Hbx Promotes the Degradation Of The Structural Maintenancmentioning
confidence: 93%
“…Recently, HBx has been reported to function by recruiting the DDB1 ubiquitin ligase to degrade SMC5/6, a putative negative regulator of HBV transcription (Decorsiere et al, 2016; Murphy et al, 2016). HBx has been reported to also work via AP-2, CREB, TFIIB, TFIH and has also been thought to oppose the cccDNA repressive activities of host protein Spindlin 1 and possibly to “overcome” SETDB1 mediated H3Kme3 and HP1 condensation of cccDNA (Riviere et al, 2015).…”
Section: Transcription Of Cccdna and Transport Of Rna Out Of The Nucleusmentioning
confidence: 99%
“…Exploiting the ability of SMC5/6 to repress HBV cccDNA, is certainly worth exploring, possibly by way of inhibiting the HBx poly-peptide, since HBx was reported to oppose the SMC5/6-mediated repression of HBV cccDNA (Decorsiere et al, 2016; Murphy et al, 2016). …”
Section: Transcription Of Cccdna and Transport Of Rna Out Of The Nucleusmentioning
confidence: 99%